1999
DOI: 10.1161/01.str.30.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose and Pa o 2 Modulation on Cortical Intracellular Acidosis, NADH Redox State, and Infarction in the Ischemic Penumbra

Abstract: Background and Purpose-During focal cerebral ischemia, the ischemic penumbra or border-zone regions of moderate cortical blood flow reductions have a heterogeneous development of intracellular cortical acidosis. This experiment tested the hypotheses that (1) this acidosis is secondary to glucose utilization and (2) this intracellular acidosis leads to recruitment of potentially salvageable tissue into infarction. Methods-Brain pH i , regional cortical blood flow, and NADH redox state were measured by in vivo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 67 publications
1
138
1
2
Order By: Relevance
“…NADH fluorescence has also been measured in vivo under a number of altered physiological conditions including spreading depression and ischemia (Anderson et al, 1999;Tomlinson et al, 1993;Welsh et al, 1991). In more recent reports, NADH fluorescence was imaged from the cortex following middle cerebral artery occlusion using charge coupled device (CCD) cameras (Strong et al, 1996;Strong et al, 2000).…”
Section: Nadh and Flavoprotein Autofluorescencementioning
confidence: 99%
“…NADH fluorescence has also been measured in vivo under a number of altered physiological conditions including spreading depression and ischemia (Anderson et al, 1999;Tomlinson et al, 1993;Welsh et al, 1991). In more recent reports, NADH fluorescence was imaged from the cortex following middle cerebral artery occlusion using charge coupled device (CCD) cameras (Strong et al, 1996;Strong et al, 2000).…”
Section: Nadh and Flavoprotein Autofluorescencementioning
confidence: 99%
“…However, in mammalian ischemic stroke pathologic examination, the deleterious effects of anoxia or hypoxia are compounded by impaired cerebral blood flow, which also limits nutrient delivery and slows the removal of signaling molecules, ions, and metabolically derived lactate and CO 2 (Branston et al, 1974). These events enhance cytotoxicity, ionic imbalance, and acute acidification in the occluded region (the infarct core) and hypoperfused surrounding tissue (the penumbra) (Anderson et al, 1999;Yao et al, 2007). Similarly to the mammalian ischemic penumbra, turtle brain pH becomes more acidic during anoxia (Buck et al, 1998;Wasser et al, 1991); however, cerebral blood flow is increased (Bickler, 1992) and liver glycogen stores are mobilized and continuously delivered to the brain, facilitating glycolytic ATP production (Bickler and Buck, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that in a majority of patients with acute stroke with admission hyperglycemia, hyperglycemia may be triggered by stress responses in reaction to the extensive brain injury 130, 131. Experimental evidence suggests that hyperglycemia significantly worsens both cortical intracellular brain acidosis and mitochondrial function in the ischemic penumbra, while provoking anaerobic metabolism, lactic acidosis, and free radical production 129, 132. While most experimental studies as well as clinical trials have concluded that DM and hyperglycemia are associated with poor outcome poststroke, there are, however, a few reports indicating that hyperglycemia may also extend mild protection against neuronal damage 133, 134.…”
Section: Hyperglycemia In Patients With Acute Strokementioning
confidence: 99%
“…Using 2 experimental stroke models in rodents, it has been shown that the adverse effects of hyperglycemia in stroke may critically depend on several factors: (1) the extent of collateral blood supply to the injured brain tissue, (2) the extent of local CBF decrease, and (3) the timing of hyperglycemia 134. In the ischemic border tissue, hyperglycemia increases glucose supply and promotes anaerobic metabolism converting glucose to lactic acid 132, 134. Hence, in ischemic regions receiving collateral blood flow, acidosis leads to the expansion of infarct by recruiting the ischemic penumbra into the infarction 132, 134.…”
Section: Hyperglycemia In Patients With Acute Strokementioning
confidence: 99%